The Relationship between Family Functions and Juvenile Delinquency: A Case of Nakuru Municipality, Kenya - Muola, James Muthee; Ndung’u, Mary N; Ngesa, Fredrick (International Association of African Researchers, 2009)
The incidences of juvenile delinquency have increased in recent years in Kenya. Most of the studies done on Juvenile delinquency have paid little or no attention to family functions as one of the possible causes. This study was carried out in Nakuru town Municipality on former street children on rehabilitation in three homes. The sample was 148 and included all the 30 girls in the three homes and 118 boys selected using the stratified random sampling technique from a population of 241. Three managers of the three homes and six purposively selected parents were included. Two interview schedules and a questionnaire were used to collect data from the respondents. Data was analyzed using descriptive statistics, Pearson’s moment correlation and t-test. Juvenile delinquency was found to be significantly related to marital stability, family size, marital adjustment and mode of discipline. A weak relationship between juvenile delinquency and socio-economic status was observed. The delinquency level of boys was significantly higher than that of girls. It was concluded that there is a relationship between family functions and juvenile delinquency. The study recommended strengthened of counselling on parenting and involvement of families and non-governmental organizations in the rehabilitation efforts.
Keywords: Family; Functions; Juvenile; Delinquency.